Analisis Perencanaan Strategis di Sekolah Dasar Negeri - Gati Destiyani; Andreas Resdianto; Nurul Farida; Berlian Novalita Sigalingging; Bambang Ismanto (Journal on Education, 2025)
The failure of schools to achieve their educational goals is often influenced by the lack of ability of schools to prepare strategic plans. In addition, there are still many schools that do not have strategic plans or are only prepared as a formality without being used as a guideline for school development. This article analyzes strategic planning at SDN Balerejo, with the aim of finding out the stages in the school's Strategic Planning (Renstra). This study uses a qualitative method by collecting data through direct observation and interviews with the principal. The results of the study show that in SDN Balerejo's Renstra it is prepared in a Medium-Term Work Plan (RKJM), with stages including team formation, internal and external analysis with a SWOT approach, and preparation of school strategies. In its preparation, the school also involves all stakeholders, both academic and non-academic.